Association between gut microbiota and diabetic microvascular complications: a two-sample Mendelian randomization study - Zhou, Peipei; Hao, Zhenning; Chen, Yu; Zhang, Ziqi; Xu, Weilong; Yu, Jiangyi (Frontiers in Endocrinology, 2024)
Background: Gut microbiota (GM) homeostasis in human body is closely associated with heath, which can be used as a regulator for preventing the onset and progression of disease. Diabetic microvascular complications bring about not only huge society economic burden, but also miserable mental and physical pain. Thus, alteration of the GM may be a method to delay process of diabetic microvascular complications. Objective: A two-sample Mendelian randomization (MR) analysis was conducted for revealing the causal inference between GM and three core diabetic microvascular complications, including diabetic kidney disease (DKD), diabetic retinopathy (DR) and diabetic neuropathy (DNP). Methods: First, genome-wide association study (GWAS) summary statistics for GM from the MiBioGen consortium and three main diabetic microvascular complications acquired from the FinnGen research project were assessed. Second, a Forward MR analysis was conducted to assess the causality of GM on the risk of DKD, DR and DNP. Third, a series of sensitivity studies, such as heterogeneity tests, pleiotropy evaluations, and leave-one-out analyses, were further conducted to assess the accuracy of MR analysis. Finally, Steiger tests and reverse MR analyses were performed to appraise the possibility of reverse causation. Results: 2092 single nucleotide polymorphisms related to 196 bacterial traits were selected as instrumental variables. This two-sample MR analysis provided strongly reasonable evidence that 28 genetically predicted abundance of specific GM acted non-negligible roles in the occurrence of DKD, DR and DNP complications was causally associated with 23 GM, the odds ratio of which generally ranged from 0.9 to 1.1. Further sensitivity analysis indicated low heterogeneity, low pleiotropy and high reliability of the causal estimates.The study raised the possibility that GM may be a potential target to prevent and delay the progression of diabetic microvascular complications. Further experiments of GM therapy on diabetic microvascular complications are warranted to clarify their effects and specific mechanisms.